The Law Enforcement of Stock Pump and Dump Practices by Influencers through Act No. 4 of 2023 concerning Development and Strengthening of the Financial Sector - Sitorus, Yosua Audric Matthew; Dirkareshza, Rianda (Law Development Journal, 2023)
The practice of stock pump and dump involving influencers such as Belvin Tannadi has become a significant concern in Indonesia following the introduction of the P2SK Law, which expands the legal scope of this practice. This article aims to examine the legal implications of pump and dump practices by influencers in Indonesia, particularly after the revision of Act No. 8 of 1995 as amended by Act No. 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law). This research uses a normative legal approach by applying a statute approach and a case approach to analyze the legal ramifications of pump and dump practices by influencers and their law enforcement in Indonesia. The results show that the perpetrators of the practice of pump and dump shares, especially influencers who violate this provision, may be subject to severe sanctions as stipulated in Article 22 paragraph (43) of the P2SK Law in conjunction with Article 104 of the PM Law with a minimum imprisonment of 5 years to a maximum of 15 years and a minimum fine of five billion rupiah and a maximum of one hundred and fifty billion rupiah. Although Indonesia has taken a step forward in capital market regulation by removing the word "material" from the P2SK Law, law enforcement against this practice still needs to improve speed and firmness. The Belvin Tannadi case demonstrates that the OJK needs to take tangible action, whereas, in the United States, law enforcement appears to be more efficient. Furthermore, safeguarding the integrity of Indonesia's capital market and investors from harmful practices hinges on collaboration among law enforcement agencies, prioritizing investor education, and enhancing transparency and accountability in handling cases.